PREDICTION OF HOLE ACCURACY BY USING LASER MACHINING - Kariem Shather, Saad; Abd Al Jabar, Zainb (Journal of Engineering and Sustainable Development, 2020)
The aim of this study is to predict the hole accuracy which drilled by laser beam machining using Response Surface Methodology (RSM) within Minitab 17. ANOVA program and compare the results with the experimental values which performed under different cutting conditions Cutting speed (2, 2.5, 3, 3.5, 4 m/min ) with power ( 600, 700, 800, 900, 1000 watt ) and gas pressure assist ( 2, 3 ,4, 5,6 bar ) so another parameters that using during operation remain constant. Experiments were conducted to predict the hole accuracy, the estimated result shows that there is good agreement between average experiments values and predicted values of hole accuracy (95.96%).